Quantitative computation and stability evaluation of phase III composition comprising sitagliptin and dapagliflozin propanediol monohydrate by RP-HPLC - Yesha Darshak Patel, Pinak Rameshbhai Patel, Jigna Bhatt, Binny Mehta, Krunal Detholia (Journal of Applied Pharmaceutical Science, 2022)
It is always quite essential to evaluate stability performance of any formulation before it enters into the commercial market or available for the clinical trial and so is the case with formulation containing sitagliptin and dapagliflozin propanediol monohydrate, which is at present in clinical phase-III trial. With the same perspective, a reverse phase high performance liquid chromatography was engineered for quantification of both components in presence of their degradation products formed during stress testing. Elution was achieved on Inertsil ODS C18 column with Methyl Nitrile (25 parts) and 0.02 M KH2 PO4 buffer 0.02 M having 1 ml triethylamine with neutral pH adjusted by orthophosphoric acid (75 parts) in isocratic mode (flow rate of 1 ml/minute), while chromatogram was monitored at 210 nm. All system suitability parameters are indicative of excellent separation. Analysis of stressed samples (according to ICH Q1) showed that the household formulation showed oxidative instability and overall results of forced stress were predictive in nature. The optimized analytical technique was subjected to validation (according to ICHQ1 guideline) and was observed to be highly reproducible with greater level of specificity, and therefore can be practiced for routine quantification of sitagliptin and dapagliflozin propanediol monohydrate from proposed formulation.
Keywords: Sitagliptin, dapagliflozin propanediol monohydrate, forced degradation, RP-HPLC, analytical method validation